RELASI ISLAM DAN NASIONALISME DALAM SEJARAH BANGSA INDONESIA - Suhaimi, Suhaimi (Al Qalam, 2013)
In line with the times demand, nationlism changes as a dynamic of dialectics proceeds with changes in social, political, and ekonomic in the country and global levels. Based on a review of historical chronology, this paper analyzed descriptively the relationship between Islam and nationalism in Indonesia. Since the early growth of nationalism and the Dutch colonization period in Indonesia, Islam became the spirit of sacrifice of lives and property of the Indonesian people's fighting to get independence and on the Japanese colonial period and the early days of independence, Islam through the muslim leaders founction as base of departure and developer awareness of nasionalism, patriotism and unity to defend the independence. Despite the authoritarian New Order ruler cope with Islam through the establishment of the Association of Indonesian Muslim Intellectuals (ICMI), but awareness of national Muslim leaders to build Indonesia managed to push governance reforms. And in this era of reform, the spirit of nationalism and the spirit of sacrifice of the Indonesian leaders increasingly eroded by corruption. Key words: proto-nationalism, political nationalism, cultural nationalism.